Pelatihan Bahasa Inggris untuk Guru Sekolah Dasar di Yogyakarta di Masa Pandemi Covid-19 - Adaninggar Septi Subekti; Maria Raras Rumanti (Jurnal Pengabdian Pada Masyarakat, 2020)
ENGLISH TRAINING FOR ELEMENTARY SCHOOL EDUCATORS IN YOGYAKARTA IN THE TIME OF COVID-19. This community service activity was conducted in the form of an English training for eight teachers of an Elementary School in Yogyakarta, Indonesia. It was conducted from January 2020 up to April 2020. The elementary school in which the training was conducted was an inclusive school in the process of implementing English as Medium Instruction (EMI) policy. As such, its teachers’ mastery of English became paramount important to facilitate young learners with all their individual differences. The training consisted of ten meetings focusing on giving instructions in class. The first up to the sixth meetings were conducted at the school in a face-to-face mode, whilst the seventh up to the tenth meetings were conducted online, mostly through tele-conferences, due to the Covid-19 pandemic compelling both facilitators and the training participants to work from home. In the ninth meeting, the participants sent their micro-teaching videos on giving effective instructions in class. In the last meeting, the facilitators gave constructive feedback based on the videos sent earlier on aspects that the participants had been good at and aspects that still needed improvements.